EFFECTIVENESS OF VIDEO AND LEAFLETS ON KNOWLEDGE AND ATTITUDES IN DYSMENORRHEA SELF-MEDICATION - Nada Utami Manalu; Sri Mulyani; Yulia Indah Permata Sari; Muthia Mutmainnah; Meinarisa Meinarisa (Jurnal Multidisipliner Kapalamada, 2026)
Adolescence is a transitional period characterized by rapid physical and psychological development, including the onset of menstruation. Dysmenorrhea is a common problem among adolescent girls and can negatively affect daily activities, academic performance, and quality of life. In Indonesia, menstrual pain remains highly prevalent, as reported by the World Health Organization globally and supported by local studies. This study aimed to determine the effectiveness of video and leaflet educational media in improving knowledge and attitudes regarding self-medication for dysmenorrhea using turmeric and tamarind herbal medicine. A quasi-experimental pretest–posttest control group design was conducted at SMP Negeri 11 Jambi City, Jambi City, Indonesia. Results showed that both media significantly improved knowledge, while no significant difference was found in attitude change between groups. Educational interventions effectively enhance adolescents’ understanding of dysmenorrhea management.